EP493 Does ultra-staging with immunohistochemistry improve the detection of metastasis in sentinel lymph nodes in endometrial cancer?. (1st November 2019) - Chaowawanit, W; Campbell, V; Wilson, E; Chetty, N; Perrin, L; Jagasia, N; Barry, S
Abstract : Introduction/Background: Ultra-staging with immunohistochemistry (IHC) increases the detection of sentinel lymph node metastasis in endometrial cancer. The aims of this study were: To determine the percentage of positive SLN identified on ultra-staging with IHC which were negative on H&E. To determine if the ultra-staging/IHC result altered the prescription of adjuvant therapy. Methodology: 120 women with histologically confirmed endometrial cancer, treated with a minimally invasive hysterectomy, BSO and SLN mapping were included. All mapped SLNs were histopathological confirmed. If no macroscopic metastasis were identified on H&E staining, ultra-staging with IHC was performed. Results: SLNs of 103 patients were included in the histopathological analysis. Ninety eight percent (101/103) of all, had ultra-staging performed. Positive SLNs were identified in 7 cases. Two cases had macroscopic metastasis on H&E staining. Using our ultra-staging protocol, 5 patients (5%) had positive SLNs (3 had microscopic metastasis and 2 had isolated tumour cells). According to the Queensland Centre for Gynaecological Cancer (QCGC) protocol for adjuvant therapy, 14 of 101 patients (14%) had their adjuvant treatment altered based on the SLN status after ultra-staging. Conclusion: Ultra-staging with IHC increased the detection of positive SLNs. Ultra-staging decreased the prescribed adjuvant therapy in 14% of our patients. Disclosure: Nothing to disclose.